2006
DOI: 10.1159/000094955
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Arteriovenous Malformation Radiosurgery on the Brain: From Morphology and Perfusion to Neurocognition

Abstract: The therapeutic aims of brain arteriovenous malformation (AVM) radiosurgery are multiple. Protecting patients from rebleeding is the prime goal. Among the others, hemodynamics, perfusion and neurocognition recovery are interesting and important. Anatomically AVM contains an abnormal cluster of vascular networks (nidus) between arteries and veins. Hemodynamically the nidus contains a low resistance and causes high-flow transnidal shunts between both sides of the nidus. The shunts cause hypotension in the neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…This was not emphasized in the results because various reports in the literature show minimal sequelae of stereotactic radiosurgery treatment on cognitive function. [23][24][25] Patients in a poor clinical state after initial hemorrhage, or as a result of active treatment, were not evaluated. In our opinion, neuropsychological testing is a fine tool that can be used to measure and compare outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This was not emphasized in the results because various reports in the literature show minimal sequelae of stereotactic radiosurgery treatment on cognitive function. [23][24][25] Patients in a poor clinical state after initial hemorrhage, or as a result of active treatment, were not evaluated. In our opinion, neuropsychological testing is a fine tool that can be used to measure and compare outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A case series which included three pre-adolescents (age 10 and 11) and two adolescents (age 15), considered to be cognitively intact before AVM discovery, showed that regardless of the AVM location, mild to moderate executive dysfunction was evident after surgical excision of the AVM (Whigham and O'Toole 2007). In contrast, a study on neurocognition and radiosurgery in adults (N=34) demonstrated that AVM patients improved significantly (p<0.001) on the Wisconsin Card Sorting Test (WCST) after radiosurgical treatment (Guo et al 2006). Because executive functions are thought to develop during adolescence, Whigham and O'Toole suggested that AVM treatment in their adolescent patients may help explain the vulnerability towards executive dysfunction after AVM treatment.…”
Section: Neurological/neuropsychological Deficitsmentioning
confidence: 99%
“…Very few studies have addressed the issue of the possibility of cognitive dysfunction in patients who undergo radiosurgery. [ 6 7 8 9 10 ] The present study evaluated a cohort of patients with brain AVMs prospectively and compared the pretherapeutic neuropsychological scores with 2 years posttreatment scores. To the best of our knowledge, this study represents one of the largest series where cognitive outcome after 2 years of patients with AVMs treated with gamma knife radiosurgery (GKRS) has been evaluated.…”
Section: Introductionmentioning
confidence: 99%